Effect of Oxidants on Properties of Electroactive Ultrathin Polyazulene Films Synthesized by Vapor Phase Polymerization at Atmospheric Pressure - Yewale Rahul; Damlin Pia; Kvarnström Carita (Amer Chemical Soc, 2023)
A non-benzenoid aromatic hydrocarbon azulene, naturally found in plants and mushrooms, is known for its derivatives applications in medicines. However, the processability of its chemically synthesized high-capacitance polymer is constrained by the sparingly soluble nature of its polymeric form. Oxidative chemical synthesis on a desirable substrate overcomes this difficulty. In this report, polyazulene (PAz) thin films are synthesized by vapor phase polymerization at atmospheric pressure using oxidants, such as CuCl2, CuBr2, FeCl3, and FeTOS. The effect of oxidants on morphologies of PAz films is studied using atomic force microscopy and microscope imaging. Each oxidant produced distinct microstructures in the films. The films synthesized using Cu(II) salts showed organized and knitted structures, whereas Fe(III) salts formed casted sheet-like disordered arrangements. The films synthesized using CuCl2 created uniform porous film assemblies. The pre-peak formations and their splitting observed in the cyclic voltammograms revealed phase segregations in the films. Oxidant-dependent structural and chemical differences such as charge carrier formation, doping levels, and polymer chain length in the PAz films are studied by using UV-Vis and FTIR spectroscopy. The results indicated that 240 and 180 mM are the optimum concentration of CuCl2 to produce high capacitance and well-organized single-and triple-layered PAz films, respectively.